Environmental licensing screening in Espírito Santo state: the practice for small Hydroelectric Power Plants - Veronez, Fernanda Aparecida; Estevam , Maria Stella Sena; Almeida, Maria Rita Raimundo e (Sustainability in Debate, 2022)
In the context of Environmental Licensing (EL), project screening is an essential process that establishes whether Environmental Impact Assessment is needed or not. This paper analyzes the EL screening of a type of Small Hydroelectric Power Plants (less than 3 MW) in Espírito Santo state and compares it with other states in Brazil. The methodological process involved document analysis, good practices criteria application, and comparative analyses of the case study. The document analysis allowed us to understand how EL procedures in Espírito Santo have changed over time. The good practices criteria application allowed us to discuss how well processes aligned with outlined objectives. Finally, the comparative analysis between Espírito Santo and other Brazilian states allowed us to identify possible improvements for Espírito Santo’s EL system. For example, screening could be improved by considering environmental sensitivity metrics for project classification and establishing guidelines for case-by-case analyses.